(untitled) (The Research of Medical Science Review, 2025)
Background Handgrip strength (HGS) predicts the hand function, physical fitness, and nutritional status; however, the body mass index (BMI) shows the presence of obesity and malnutrition. To evaluate the correlation between the two, both parameters are significant. Objective To determine the effects of body mass index on hand grip strength in Physical therapists. Methodology A cross-sectional study approach was used in this research to investigate the effects of Body Mass Index (BMI) on Hand Grip Strength in physical therapists. A questionnaire was distributed among a sample size of 125 physical therapists of both sexes were divided into Group A (62 males) and Group B (63 females) using a non-probability purposive sampling technique. The hand grip strength of the dominant hand was measured through a hand-held dynamometer. Data was analyzed through SPSS Statistics software version 23.0. The questionnaire covered demographics, grip strength, Body Mass Index, physical activity, and injury-related questions. Result A total of 125 physical therapists participated in the study, comprising 62 males and 63 females. Among them, 14.4% were underweight, 65.6% had normal BMI, and 20% were overweight. Male participants demonstrated significantly higher hand grip strength compared to females. In males, 17.6% had weak HGS, 17.6% normal, and 14.4% strong. Among females, 32.8% had weak HGS, 16.0% normal, and only 1.6% strong. The dominant hand consistently showed greater strength across all participants. Overall, individuals with normal BMI tended to have better grip strength than those who were underweight or overweight. Conclusion Our study concluded that male participants had stronger hand grip strength as compared to females.